In knowledge management, nothing is created, nothing is lost, everything is transformed? A critical analysis of solid waste in health and its impacts on the environment (Research, Society and Development, 2022)
Healthcare waste is waste generated by companies that serve human or animal health, including common waste and waste that may be infectious or hazardous to human health and the environment. Brazilian law stipulates that generators are responsible for the correct treatment and environmentally appropriate final disposal of this waste. In order to analyze the management of knowledge in the treatment of solid waste from health services, describing the management actions and selective collection of these wastes, a bibliographic, analytical and descriptive survey was carried out based on previously published material, carried out in libraries and internet, consisting of books and articles published in the last 10 years and classics, where access is allowed. It is concluded that the Solid Health Waste management plan is very important for any health institution and giving the proper destination to waste is everyone's responsibility and must be supervised by competent bodies. Thus, knowledge management is necessary to protect the environment and human beings so that they can live in a healthy and balanced environment.